Prevotella species as oral residents and infectious agents with potential impact on systemic conditions - Könönen Eija; Fteita Dareen; Gürsoy Ulvi K; Gürsoy Mervi (United Kingdom, 2022)
Oral Prevotella are known as anaerobic commensals on oral mucosae and in dental plaques from early life onwards, including pigmented P. melaninogenica, P. nigrescens, and P. pallens and non-pigmented Prevotella species. Many Prevotella species contribute to oral inflammatory processes, being frequent findings in dysbiotic biofilms of periodontal diseases (P. intermedia, P. nigrescens), cariotic lesions (P. denticola, Alloprevotella (formerly Prevotella) tannerae), endodontic infections (P. baroniae, P. oris, P. multisaccharivorax), and other clinically relevant oral conditions. Over the years, several novel species have been recovered from the oral cavity without knowledge of their clinical relevance. Within this wide genus, virulence properties and other characteristics like biofilm formation seemingly vary in a species- and strain-dependent manner, as shown for the P. intermedia group organisms (P. aurantiaca, P. intermedia, P. nigrescens, and P. pallens). Oral Prevotella species are identified in various non-oral infections and chronic pathological conditions. Here, we have updated the knowledge of the genus Prevotella and the role of Prevotella species as residents and infectious agents of the oral cavity, as well as their detection in non-oral infections, but also gathered information on their potential link to cancers of the head and neck, and other systemic disorders.